Total Syntheses of Cylindrocyclophanes Exemplifying the Power of Transition-Metal Catalysis in Natural-Product Synthesis - Berthold, Dino; Breit, Bernhard (Synlett, 2020)
Cylindrocyclophanes are a class of naturally occurring 22-membered macrocycles with a unique architecture and interesting physical, chemical, and biological properties. This comprehensive account summarizes progress in various synthetic approaches to these compounds during the last twenty years, thereby emphasizing the key steps for establishing the [7,7]-paracyclophane scaffold, as well as alternative approaches to the construction of its stereocenters. Many of these syntheses highlight the power of transition-metal catalysis for natural-product synthesis. Furthermore, the unraveling of the biosynthesis to these natural products in Cylindrospermum licheniforme is discussed.1 Introduction2 Biosynthesis3 Smith’s Synthesis of (–)-Cylindrocyclophanes A and F4 Hoye’s Synthesis of (–)-Cylindrocyclophane A5 Iwabuchi’s Syntheses of (–)-Cylindrocyclophane A and (+)-Cylindrocyclophane A6 Nicolaou’s Synthesis of (–)-Cylindrocyclophanes A and F7 Breit’s Synthesis of (–)-Cylindrocyclophane F8 Conclusion
Keywords: cylindrocyclophanes; total synthesis; transition-metal catalysis; dimerization; biosynthesis